Cost analysis and utility index in congestive heart failure patients in Hospital Dr. Moewardi Surakarta: bahasa inggris - Lering, Maria Nona Adriani; Andayani, Tri Murti; Purwidyaningrum, Ika (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Congestive heart failure is a progressive disease that causes a decreased quality of life, increases the need for medical expenses, and has a long treatment time. The purpose of this study is to analyze the cost of treatment and see the utility index in patients with congestive heart failure at RSUD Dr. Moewardi Surakarta. Method: The research method used a cross-sectional design, data were collected retrospectively from medical records, financial data, and pharmaceutical installations to see data on direct medical costs and utility data using the EQ-5D-5L questionnaire during March-May. The subjects of the study were 78 outpatient heart failure patients at RSUD Dr. Moewardi Surakarta with inclusion criteria, namely heart failure patients aged > 40 years and complete medical record data including age, sex, comorbidities, degree of severity, and drug therapy. Results: Data were analyzed using the Man Whitney U test and the Kruskal Walis H test. The results of this study showed direct medical costs, namely pharmacy (Rp. 2,837,328.00), service fees (Rp. 150,000.00), medical procedures (Rp. 89,717.95), and administrative fees (Rp. 10,000.00). Total direct medical costs Rp. 3,087,045.95. The results of the EQ-5D-5L questionnaire based on each dimension were 78.2% no problems with walking ability, 97.4% no problems with self-care, 59.0% no problems with activities, 34.6% little had problems with pain, and 57.7% had no problems with anxiety/depression. The utility index value is 0.803. Conclusion: The conclusion is that the average direct medical cost is Rp. 3,087,045.95 and the utility index value is 0.803.